2016
DOI: 10.1186/s40639-016-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging compassion through teaching and learning: a case study in Cyprus

Abstract: Background: It has been suggested that the biomedical approach towards healthcare professional training may neglect the humanistic nature and personal values of care. As such, discussions with regard to the importance of introducing compassion training into undergraduate programmes and throughout professional practice are of interest. Within this paper, we report on a compassionate care programme designed for, and delivered to, healthcare professionals and managerial/administrative staff at a private hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They reported that they became re-invigorated and more engaged. Similar to Shea et al's (2016) evaluation of a Compassionate Care Program for nurses, the majority of the leaders in the current study commented on the innovativeness and experiential nature of the strategies used to enhance earning. Moreover, a number of leaders stated that the program helped boost their confidence and self-awareness, equipped them with presentation skills, and enabled them to understand the different personalities within the workplace.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…They reported that they became re-invigorated and more engaged. Similar to Shea et al's (2016) evaluation of a Compassionate Care Program for nurses, the majority of the leaders in the current study commented on the innovativeness and experiential nature of the strategies used to enhance earning. Moreover, a number of leaders stated that the program helped boost their confidence and self-awareness, equipped them with presentation skills, and enabled them to understand the different personalities within the workplace.…”
Section: Discussionmentioning
confidence: 85%
“…A number of contemporary nurse scholars emphasized the importance of compassionate care in nursing (Bramley & Matiti, 2014;Maxwell, 2017;Tierney, Seers, Reeve, & Tutton, 2017). However, terms such as caring, compassion, empathy and sympathy are often used interchangeably in practice, without a full understanding of their meaning (Francis, 2013;Sinclair et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…May we have different strategies in teaching but at the end of the day we have the same purpose." (IDI2) It appeared that compassion in teaching enhanced sustainability (Shea et al, 2016). Similarly, teaching must highlight love and compassion because it could enhance learning (Miller, 2019).…”
Section: Pieces Of Advice Shared To Teachersmentioning
confidence: 99%
“…Worldwide, it seems to be an agreement on how compassionate care may be enhanced through organisational design, education and training programmes (Saab et al, 2019), not only for front line health professionals, but also for managers and policy makers (Shea et al, 2016). In a programme that was implemented in Cyprus titled ‘Cultivating compassion in hospitals—improving quality of care, Limassol, Cyprus, 2015’ a practical framework was developed for providing compassion for oneself and others.…”
Section: Introductionmentioning
confidence: 99%
“…In a programme that was implemented in Cyprus titled ‘Cultivating compassion in hospitals—improving quality of care, Limassol, Cyprus, 2015’ a practical framework was developed for providing compassion for oneself and others. The educational course was expected to improve the quality of care through improvement of the organisational culture, collaboration and communication (Shea et al, 2016). In line with this, a survey on nursing (self) assessment of soft skills in Cyprus showed that managers and nurses understand the contribution and necessity of developing soft skills such as communication, empathy, team work and assertiveness in building relationships with colleagues (Zafiropoulou & Kanari, 2017).…”
Section: Introductionmentioning
confidence: 99%